Gender and social norms in Ancient Israel, Early Judaism and Early Christianity: Texts and Material Culture - Bauks, Michaela; Galor, Katharina; Hartenstein, Judith (Journal of ancient Judaism, 2019)
The aim of the present conference volume is to study the interrelationship of literary and material approaches to historical investigation of gender. Paradigmatically the significance and meaning of gender and sexuality is explored in the context of private and public, religious and secular spaces. Historical, cultural, and social norms (and deviations) of daily life are examined through the lens of textual, archaeological, and art historical investigations to interpret relics of ancient Israelite, Jewish, and Christian communities from the Iron Age through Late Antiquity. Scholars from varied disciplines such as biblical and classical archaeology, epigraphy, Old and New Testament exegesis and religious studies assembled to engage in a dialogue involving both texts and material culture.